Neurocysticercosis and HIV Infection: what can we learn from the published literature? - Herrera Vazquez, Omar; Romo, Matthew L.; Fleury, Agnès (Arquivos de Neuro-Psiquiatria, 2019)
Infections caused by the human immunodeficiency virus (HIV) and by the larvae of Taenia solium (i.e., cysticercosis) are still widespread in many developing countries. Both pathologies modify host immune status and it is possible that HIV infection may modulate the frequency and pathogeny of cysticercosis of the central nervous system (i.e., neurocysticercosis [NCC]).Objective: To describe published cases of NCC among HIV-positive patients and to evaluate whether the characteristics of NCC, including frequency, symptoms, radiological appearance, and response to treatment differed between HIV-positive and HIV-negative patients.Methods: Forty cases of NCC/HIV co-infected patients were identified in the literature. Clinical and radiological characteristics, as well as response to treatment, were compared with non-matching historical series of NCC patients without HIV infection.Results: Most of these patients had seizures and multiple vesicular parasites located in parenchyma. Clinical and radiological characteristics were similar between HIV-positive and HIV-negative patients with NCC, as well as between immunocompromised and non-immunocompromised HIV-positive patients.Conclusion: Our review did not reveal clear interactions between HIV and NCC. This may be partially due to the small number of cases and reliance on published research. A systematic, multi-institutional effort aiming to report all the cases of this dual pathology is needed to confirm this finding and to clarify the possible relationship between both pathogens.
Keywords: HIV; coinfection; Taenia solium; neurocysticercosis